The Effect of Educational Activities through the Flipped Classroom on Students with Low Metacognitive Thinking - Zaki, Marwa Zaki Tawfiq; El-Refai, Walid Yousry; Najmi, Ali Hassan; Al-Hafdi, Fahad Saleem; Alhalafawy, Waleed Salim; Bakey, Fatma Mohamed Abd El; Bakey, Fatma Mohamed Abd El (Journal of Ecohumanism, 2024)
The "flipped classroom" approach has gained popularity in the field of education, especially in the post- Covid-19 era. The flipped classroom approach involves a variety of instructional activities that take place both inside and outside the classroom. Therefore, it is crucial to determine the most efficient way for organizing flipped classroom activities. As metacognitive thinking skills are one of the basic skills required for learning in the context of digital technologies, the current research aimed to investigate the impact of two type of flipped classroom activities, namely self-directed activities (SDA), and sequence task activities (STA), on metacognitive thinking skills. This investigation was conducted in recognition of the fundamental role that metacognitive thinking skills play in the process of learning within the realm of digital technologies. The research used a quasi-experimental methodology to conduct a comparative analysis of the two experimental groups. The first experimental group utilized a flipped classroom approach which is characterized by self-directed activities, whereas the second experimental group utilized a flipped classroom model centered on sequential tasks. The study sample included (60) high school students who were assigned to the two research groups using a random distribution method. A metacognitive thinking scale was devised, including three distinct dimensions: planning, monitoring, and assessment. The findings of the study demonstrated that flipped classrooms, which include self-directed activities, exhibit a higher level of efficacy in fostering the development of metacognitive thinking abilities. The study suggested the need of enhancing the structure of flipped classrooms based on the self-directed activities framework.